Molekularpathologie bei urologischen Tumoren: Empfehlungen der Konsenskonferenz der Internationalen Gesellschaft für Uropathologie (ISUP) 2019 - Hommerding, Oliver; Allory, Yves; Argani, Pedram; Bismar, Tarek A.; Bubendorf, Lukas; Canete-Portillo, Sofía; Chaux, Alcides; Chen, Ying Bei; Cheng, Liang; Cubilla, Antonio L.; Egevad, Lars; Gill, Anthony J.; et al. (Pathologe, 2021)
Comprehensive understanding of molecular principles in cancer and the diversification of oncological therapy promise individual therapeutic concepts, which have not yet found their way into urogenital cancer therapy. In March 2019 the International Society of Urogenital Pathology (ISUP) therefore held a consensus conference on recommendations for molecular diagnostics of genitourinary tumors, which were published in five separate manuscripts and are summarized in this article. In preparation for the conference, a comprehensive survey of current practices for molecular testing of urogenital tumors was carried out by members of the ISUP. At the conference, the results and the corresponding background information were presented by five working groups and recommendations for action for diagnostics were developed. An agreement between 66% of the conference participants was defined as consensus.
CRIS-Team Scopus Importer:2021-01-15
Keywords: Bladder cancer; Kidney cancer; Molecular biomarker; Prostate cancer; Targeted therapy